Animals and disease : - Wilkinson, Lise (Cambridge University Press, 1992)
Animals and Disease examines the interactions of medicine and veterinary medicine in their common quest for ways of combating and controlling epidemic diseases in man and animals. Emphasis is placed on the study of animal disease itself, and its implications for human medicine, at first empirically, and later by deliberate use of animal models. Following a general introduction, the text is mainly concerned with developments of the eighteenth and nineteenth centuries, focusing in particular on the apparent paradox of the founding of the Brown Institution in London, an institute for comparative medicine, nearly twenty years before similar institutes appeared in France and in Germany, although comparative medicine was studied with much more enthusiasm there than in the British Isles. The rise and fall of the Brown Institute and the subsequent rise of the great institutes of Paris and Berlin is discussed, concluding with the rise at the turn of the century of American institutes for comparative medicine.